Non-Gaussian fatigue analysis of packaged fruit under random vibration using an improved CEEMDAN hybrid Gaussian decomposition approach - Song-Ping Yang; Jun-Ye He; He-Mu Yu; Tong Ji; Zhi-Wei Wang (Postharvest Biology and Technology, 2026)

Fibrotic microRNAs in the suppression of HSC activation and ECM deposition to facilitate the regression of hepatic fibrosis in zebrafish - Yu-Heng Lai; Mu-Kuang He; Chung-Tsui Huang; Han-Yu Tseng; Tzu-Ching Lin; Ting-Yu Yang; Semon Wu; Guor Mour Her (Journal of Molecular Medicine, 2026)
During liver injury, early pathological changes may go unnoticed, delaying the diagnosis until the disease has advanced to stages such as fibrosis, cirrhosis, or hepatocellular carcinoma. Hepatic fibrosis is a sign of long-term liver injury that leads toward permanent liver damage. It involves the buildup of too much extracellular matrix (ECM) and is activated by hepatic stellate cells (HSCs). The transforming growth factor-β1 (TGF-β1)/SMAD pathway is central to this process, which shows great potential for therapeutic strategies. Therefore, we investigated the therapeutic potential of microRNA (miRNA)-mediated regulation of fibrogenesis by using zebrafish models. A group of fibrosis-related miRNAs was identified and used to generate transgenic zebrafish lines. Fibrosis was induced via doxycycline (DOX)-controlled overexpression of TGF-β1a, and the antifibrotic efficacy of miRNAs was evaluated. Quantitative real-time PCR showed a marked downregulation of the target miRNAs, accompanied by decreased expression of fibrotic markers. Next, we confirmed that TGF-β1a, GREM1, and α-SMA protein levels were decreasing. Histological staining revealed improved liver structure and diminished collagen deposition. These findings indicate that through manipulating the miRNA expressions, we can effectively disrupt TGF-β-induced fibrogenesis, inactivate HSC, inhibit ECM remodeling, and attenuate liver fibrosis, and highlight the potential of miRNA-based therapeutic strategies for early intervention in liver disease. Key messages Establishment of an in vivo model for developing an inducible miRNA expression system in zebrafish. Predicting and evaluating targeted miRNAs that attenuate TGF-β-induced hepatic fibrosis. Elucidate the potential mechanism for fibrosis that may be a strategy for future therapies. Graphical Abstract MicroRNA-mediated modulation attenuates hepatic fibrosis by coordinately suppressing the TGF-β/SMAD signaling pathway, hepatic stellate cell activation, and extracellular matrix deposition. Protein-level validation confirms reduced phosphorylation of Smad2 and decreased expression of key fibrotic markers, including α-SMA, collagen I, and fibronectin. These findings highlight a multi-target regulatory mechanism through which miRNAs exert antifibrotic effects at the systems level.

Spatiotemporal predictive modeling for coastal phytoplankton based on the Tapnet model: A case study in Zhejiang, China - Yan Wei; Haibin Han; Qinglin Mu; Haodi Zhu; Yueyi Qiao; Shaojian Yang; Chaoyi Yu; Na Wei; Hanyan Luo; Luyuan Zhao; Xuping Zhuo; Yufan Yuan; et al. (Marine Pollution Bulletin, 2026)

Boron-mediated pectin demethylesterification improves Na+ retention in root cell wall and alleviates salt stress in Brassica napus L. - Yu Yang; Wenjing Hao; Rui Jing; Xiaolei Feng; Diqing Yin; Muhammad Riaz; Mu Lu; Yusheng Niu; Lei Yan (Plant Science, 2026)

A probabilistic prediction model based on uncertainty quantification and interpretable deep learning: Application to runoff prediction in the Yellow River mainstream - Liang Mu; Junxi Chen; Zhiguo Yu; Hong Zhao; Zhibo Yang (Journal of Hydrology, 2026)

Pyrethrin II impairs mitochondrial potential through ROS and MAPK pathways in HT‑22 cells - Jiaojiao Gao; Xinbi Zhang; Qie Mu; Yurong Liu; Hong Yang; Rui Cao; Xiuwei Wang; Baofeng Yu; Li Zhang; Yaoyao Guo (NeuroToxicology, 2026)

METTL18-catalyzed histidine methylation of YTHDF2 promotes mRNA stability - Wen-Lan Yang; Meng-Xia Liu; Yue Han; Xing-Xing Li; Ye Gu; Xinyuan Tian; Mengqian Mu; Xiaolin Zhang; Yanzhe Wang; Xinyu Li; Yu-Sheng Chen; Chun-Chun Gao; et al. (Science China Life Sciences, 2026)

Long-range transported dust enhances ice nucleating particle abundance in the North China Plain - Yue Sun; Yujiao Zhu; Hengde Liu; Lanxiadi Chen; Hongyong Li; Yujian Bi; Di Wu; Xiangkun Yin; Can Cui; Ping Liu; Yu Yang; Jisheng Zhang; et al. (Journal of Environmental Sciences, 2026)

Deoxynivalenol impairs intestinal epithelial proliferation by disrupting the DEK-RPS6KB1 complex to suppress Wnt/β-catenin signaling - Lingjie Zeng; Ruqin Lin; Zhitian Yang; Danni Yu; Jintao Xu; Ziwan Qu; Zhikai Wu; Peiqiang Mu; Jun Jiang; Dongsheng Yao; Jikai Wen; Yiqun Deng (Journal of Environmental Sciences, 2026)

Deciphering the mechanisms underlying regional heterogeneity of high-temperature Daqu through integrated electronic sensory, volatilome, and microbiome analysis - Yu Mu; Hong Zhang; Yingdong Pan; Ziyou Tian; Ying Huang; Liang Yang; Chunlin Zhang; Chi Zhao; Dong Li; Xudong Liu; Li Jiang (International Journal of Food Microbiology, 2026)

Cl−-repelling Mn3O4/Co(OH)2 heterojunction on self-supporting N-doped CNTs for high-stability seawater zinc-air batteries - Lin Mu; Yuxin Yao; Haibo Zhao; Shifang Yang; Ying Wang; Peng Yu (Chemical Engineering Journal, 2026)

Grain quality, texture characteristics, and starch fine structure of ratoon rice practiced with high stubble height: Insights from panicles regenerated at different stem nodes - Wanfeng An; Mingji Yu; Ruixue Yu; Shuiyin Yang; Jiali Miao; Qingyao Huang; Jizhe Mu; Jianquan Qin; Chang Zheng; Xiaoyan Song; Quanzhi Zhao (Food Research International, 2026)

A molecular study of synergistic inhibition of methane hydrate growth with glycine-based peptides and PVCap - Huiyun Mu; Yang Liu; Lin Ding; Wenlong Wang; Xiaofang Lv; Yisong Yu; Qianli Ma; Chuanshuo Wang; Xiaoyan Li; Shidong Zhou (Fuel, 2026)

Unveiling animal death cognition: the role of social systems - Junjie Mu; Xi Yang; Yongbo Li; Yu Huan; Boyi Zhang; James R. Anderson; Rong Hou; Baoguo Li (Science China Life Sciences, 2026)

Corrigendum to ‘ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection’ [Pesticide Biochemistry and Physiology 220 (2026) 107056] - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

Intercalation-mediated bionic nano-hydrogel adhesives for robust omni-domain adhesion - Jialve Sun; Zhengzhi Mu; Tianye Yang; Hexuan Yu; Wenda Song; Zhiyan Zhang; Junqiu Zhang; Shichao Niu; Zhiwu Han; Luquan Ren (Chemical Engineering Journal, 2026)

Sequential release of photodynamic hybrid HOFs and CeO₂ via a bilayer dynamic SIS hydrogel for periodontitis therapy - Shiqing Ma; Yujia Xiao; Yang Yu; Xiaotong Liu; Jiayin Deng; Yilin Yang; Shiyu Yao; Beibei Ma; Yo Shibata; Jun Zhou; Bo Zhao; Yuzhu Mu (Chemical Engineering Journal, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Amorphous phosphate-mediated Schottky junction at Mo2N-based heterojunction interface to accelerate interfacial electron transfer for boosted photocatalytic hydrogen evolution - Yu-pei Li; Zi-xin Qi; Xiao-jing Wang; Jun Zhao; Jun Yang; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Unravelling methylmercury formation in high-altitude Tibetan thermokarst lakes - Xia Lu; Xiaosha Liu; Zhixia Yang; Liang Li; Man Yang; Yu-Rong Liu; Baohua Gu; Cuicui Mu (Journal of Hazardous Materials, 2026)

Effects of taurine on immunity and ammonia metabolism in large-scale loach under ammonia stress - Ruo-Yu Zhou; Lu Chen; Meng-Yang Hu; Mu-Xi Li; Yu-Xuan Fei; Mei Huang; Yun-Long Zhang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Carbon dots anchored onto biosynthesized CeO2/attapulgite with enhance antioxidant and light-driven antibacterial activities for food packaging - Wenting Gao; Bin Mu; Fangfang Yang; Yu Tang; Zhihe Luo; Aiqin Wang (Chemical Engineering Journal, 2026)

Genome-wide association study identifies key SNP and glutamate receptor 4 linked to heat tolerance in Zhikong scallop Chlamys farreri - Zhi Liu; Mingyi Sui; Zujing Yang; Haitao Yu; Qianqian Mu; Lijingjing Bao; Wenhui Jiang; Wei Lu; Qiang Xing; Zhenmin Bao; Xiaoting Huang (Aquaculture, 2026)

Quinone structure regulates sulfide-driven reactive oxygen species generation for aquatic pollutant degradation - Han-Qing Zhao; Ruihan Yu; Jiayi Liu; Hong Cheng; Aqiang Ding; Daijun Zhang; Yang Mu; Peili Lu (Water Research, 2026)

Corrigendum to “Gene delivery of chitosan-graft-polyethyleneimine vectors loaded on scaffolds for nerve regeneration” [Carbohydrate Polymers 290, 2022, 119499] - Yulin Wang; Ya Li; Zhongbing Huang; Bing Yang; Ning Mu; Zhaopu Yang; Min Deng; Xiaoming Liao; Guangfu Yin; Yu Nie; Tunan Chen; Hua Ma (Carbohydrate Polymers, 2026)

Comprehensive assessment of secondary metabolite diversity and in vitro anti-diabetic properties in Sanghuangporus quercicola cultured under different conditions - Mingxing Yu; Na Zhang; Xiaofeng Ma; Xiaoshuang Zhou; Shude Yang; Weihang Peng; Yin Li; Yuejun Mu; Xianhao Cheng; Rui Zhang; Yongfei Ming (Systems Microbiology and Biomanufacturing, 2026)

Design of Sn-doped MoS2 piezocatalyst for high-efficiency antibiotic degradation: mechanism and performance - Mingyang Xu; Xiang Wang; Jingyu Yu; Zhenlin Mu; Shengjun Yang; Chenxi Guo; Guoxuan Li; Yinglong Wang; Fanqing Meng (ENGINEERING Environment, 2026)

Achieving fast Zn dynamics in high-mass-loading cathode via 3D-printed hierarchical graphene architectures in zinc-ion batteries - Shixiang Yu; Yongbiao Mu; Huicun Gu; Yonglin Zhang; Shuai Zhao; Haowen Liang; Bowen Hu; Jinxing Sun; Xiaoteng Chen; Lin Zeng; Jiaming Bai; Jinglei Yang (Chemical Engineering Journal, 2025)

Golgi-associated TRAF6 as a regulator of protein convertase FURIN for insulin receptor precursor processing - Minjun Liu; Kun Zhou; Yang Sheng; Wen Zhang; Qiaoli Chen; Ziyue Chen; Xinyu Yang; Yuxin Jin; Fangtong Liu; Yinqiu Mu; Shu Su; Weikuan Feng; et al. (Science China Life Sciences, 2025)

Soil-atmosphere terpene exchanges in the tropical forest of French Guiana with nitrogen and phosphorus fertilizer application - Kaijun Yang; Joan Llusià; Zhaobin Mu; Jordi Sardans; Catherine Preece; Iolanda Filella; Romà Ogaya; Albert Gargallo-Garriga; Guille Peguero; Laëtitia M. Bréchet; Clément Stahl; Leandro Van Langenhove; et al. (Plant and Soil, 2025)

Revolutionizing toxicological risk assessment: integrative advances in new approach methodologies (NAMs) and precision toxicology - Qiu-Shuang Sheng; Bin Liu; Xiao Wang; Lei Hua; Shou-Cheng Zhao; Xiao-Zhong Sun; Mu-Yang Li; Xiang-Yu Zhang; Jia-Xu Wang; Pei-Li Hu (Archives of Toxicology, 2025)

BmeIF4E2 promotes AcMNPV infection in the silkworm, Bombyx mori, by direct interaction - Xin-Yi Ding; Jiang-Zhi Su; Wen-Jing Yu; Qian-Qian Jiao; Zuo-Min Shao; Ai-Jun Wan; Sheng Qin; Xia Sun; Xue-Yang Wang; Ding-Ding Lü; Mu-Wang Li (Pesticide Biochemistry and Physiology, 2025)

Dynamic covalent assembly of hierarchical COF hollow fibers for selective dye remediation - Huiling Chen; Xiubei Yang; Guiping Yang; Yuhe Mu; Chengbing Yu; Wei Zhang; Gaofeng Zeng (Desalination, 2025)

Comprehensive analysis of greenhouse gases emissions and microbial dynamics in glacier-fed lakes across various ablation stages - Shuang Liu; Fuyuan Mai; Meiqi Huang; Qing Yang; Xiaodong Li; Guangli Mu; Bingya Zhang; Linyuan Lu; Yu Pang; Ding He; Qianggong Zhang; Yiwen Liu; et al. (Water Research, 2025)

2.2-billion-year-old KREEP-rich volcanism on the Moon - Mu-Han Yang; Qian W.L. Zhang; Qiu-Li Li; Ross N. Mitchell; Richard W. Carlson; Zhu-Yin Chu; Yu Liu; Yi Chen; Shun Guo; Ding-Shuai Xue; Bin Su; Xu Tang; et al. (Science Bulletin, 2025)

Astaxanthin ameliorates Cr (VI) accumulation, antioxidant, digestive, apoptosis and inflammatory response - Lei Zhao; Ying Zhang; Jie Yu; Yi-Han Liu; Zhi-Hao Cai; Mu-Yang Li; Ming Liu (Regional Studies in Marine Science, 2025)

Identification of a ficolin involved in ovary reproductive immunity in Macrobrachium nipponense - Shuohan Yang; Huan Liu; Haifu Wan; Lei Yu; Xiaodong Cui; Shuai Guo; Shumei Mu; Xianjiang Kang (Fish & Shellfish Immunology, 2025)

Spirulina-derived atomically dispersed Fe–N4 sites on g-C3N4 for efficient CO2 photoreduction - Haoxian Wang; Junjie Wang; Jin Xu; Jingkai Lin; Zhongshuai Zhu; Yazi Liu; Feihu Mu; Bin Huang; Fei Yu; Chenmin Xu; Shaogui Yang; Huan He; et al. (Chemical Engineering Journal, 2025)

Ti3C2Tx/TiO2/CuO nanocomposite-based gas sensors for high-performance ethanol detection at room temperature - Ming Zhou; Xuefeng Hu; Zhiyuan Liu; Weiwei Qin; Liping Tan; Jilei Yang; Debao Yu; Qingqing Mu; Anquan Bao; Yali Bi; Wenjuan Yu; Wei Zhang (Chemical Engineering Journal, 2025)

A rapid calibration method for the discrete element model of straw fodder particle mixtures based on the UVE-PLS-GD algorithm - Ziqing Xiao; Haiqing Tian; Chunxiang Zhuo; Kai Zhao; Yang Yu; Qiaofei Mu; Xiaoyu Xue (Biosystems Engineering, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Effects of metal oxides loaded with biochar on adsorption of cationic and anionic metals: A meta-analysis - Yang Yu; Xinwei Chen; Lingxin Zhao; Shufei He; Likui Feng; Weixin Zhao; Huizhi Mu; Qingliang Zhao; Liangliang Wei (Journal of Environmental Management, 2025)

Exploring Allium mongolicum Regel flavonoids alleviation of deoxynivalenol-induced gut inflammation and flesh-quality improvement based on muscle-intestinal axis in a Channa argus model - Zhe Yu; Zhuang Xiong; Yi Wang; Zhi-Qiang Gao; Ke-Xin Lu; Ying Zhang; Mu-Yang Li; Yuan-Xi Yue (Food Bioscience, 2025)

Polyetheretherketone-based foam with low reflectivity and high electromagnetic interference shielding effectiveness suitable for harsh service environments - Liubo Liang; Tonghua Wu; Xiaohan Mei; Yu Bai; Chunqi Guo; Yanchao Yang; Guibin Wang; Shuling Zhang; Jianxin Mu (Chemical Engineering Journal, 2025)

Multidirectional energy absorption of bionic multi-cell tubes inspired by bamboo phloem - Shuang Zhang; Wenda Song; Zhengzhi Mu; Zhiyan Zhang; Jingde Yang; Hexuan Yu; Wenzheng Wu; Zhiwu Han; Luquan Ren (Chemical Engineering Journal, 2025)

Ramification of dyes for fiber-to-fiber recycling of cotton textiles - Yuanyi Shao; Bingnan Mu; Xiaoqing Yu; Yiqi Yang (Resources, Conservation and Recycling, 2025)

Boron-induced phenylpropanoid metabolism, Na+/K+ homeostasis and antioxidant defense mechanisms in salt-stressed soybean seedlings - Mu Lu; Muhammad Riaz; Kaiqing Tong; Wenjing Hao; Yu Yang; Xiaomeng Zhao; Lu Wang; Yusheng Niu; Lei Yan (Journal of Hazardous Materials, 2025)

Mesoporous high-entropy-alloy electrocatalysts via electrospinning for enhanced alkaline water electrolysis - Lu Wang; Chuhao Wang; Yuhe Mu; Jingrui Fan; Xiubei Yang; Chengbing Yu; Bing Guo; Gaofeng Zeng (Fuel, 2025)

Isolation, identification, and virulence of three strains of Beauveria bassiana from silkworms, Bombyx mori - Qiang Zhang; Wenqing Lai; Qin Li; Xiaoying Zhang; Zhan-peng Lu; Jiawei Jiang; Wenjing Yu; Zuo-min Shao; Xue-yang Wang; Mu-wang Li (Journal of Asia-Pacific Entomology, 2025)

A green technology for the close-loop recycling of vat dyed textiles - Yuanyi Shao; Bingnan Mu; Xiaoqing Yu; Alyssa Neff; Yiqi Yang (Resources, Conservation and Recycling, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

A new control strategy of sulfate-reducing microorganisms and corrosion rate from a high-temperature oil reservoir by nitrate/nitrite coupling with nitrate-reducing bacteria - Lei Zhou; Jie Gao; Yu-Xuan Li; Jun Wu; Biao Wang; Yi-Fan Liu; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Sustainable Fe(II) oxidation/reduction and release/recovery dual cycle in a multi-chamber Fe(III)/Peroxymonosulfate electrochemical system: Application, mechanism, and optimization - Minghao Yu; Meng Chen; Chenxu Yang; Jianrui Niu; Jing Zhang; Situ Mu; Ruina Zhang; Junjun Ma; Chun Liu (Chemical Engineering Journal, 2025)

HONO chemistry affected by relative humidity and ammonia in the North China Plain during winter - Haiyan Ran; Jingwei Zhang; Yu Qu; Juan Yang; Yong Chen; Yele Sun; Chaoyang Xue; Yujing Mu; Junling An (Atmospheric Environment, 2025)

Oxidative Stress-mediated Loss of Hippocampal Parvalbumin Interneurons Contributes to Memory Precision Decline After Acute Sleep Deprivation - Yu-zhu Gao; Kai Liu; Xin-miao Wu; Cui-na Shi; Qiu-li He; Hai-peng Wu; Jian-jun Yang; Hao Yao; Mu-huo Ji (Molecular Neurobiology, 2025)

Comparative lipidome revealed an increase of unsaturated lipids in Bifidobacterium animalis subsp. lactis 420 by linoleic acid supplementation - Qing Liao; Shuyan Wu; Ziyi Tang; Xi Yang; Ming Huang; Xing Weng; Xia Yu; Xiaoyuan Wang; Mu Zhang; Meijuan Xu; Xiaoqing Hu (Systems Microbiology and Biomanufacturing, 2025)

Association Between Multiple Plasma Toxic Metal and Metalloid Exposures and Hypertension in Elderly Chinese Adults - Yiwen Zhang; Xinyue Mu; Junpu Yu; Aimin Yang; Jingli Yang; Rongjie Wu; Fanhui Luo; Bin Luo; Rentong Chen; Li Ma; Jian He (Biological Trace Element Research, 2025)

Chitosan and gelatin based sprayable hydrogels incorporating photothermal and long-acting antibiotic sterilization for infected wound management with shape adaptability - Fei Wang; Xing Wang; Siwei Li; Qisen Yang; Haibo Mu; Jinyao Li; Yu Yang (Carbohydrate Polymers, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Phytocannabinoid-like meroterpenoids from twigs and leaves of Rhododendron spinuliferum - E-E Luo; Wu-Fen Yang; Zhao-Jie Wang; Ling-Yun Chen; Mu-Yuan Yu; Xiao-Dong Luo; Xu-Jie Qin (Phytochemistry, 2024)

Interpretable machine learning for weather and climate prediction: A review - Ruyi Yang; Jingyu Hu; Zihao Li; Jianli Mu; Tingzhao Yu; Jiangjiang Xia; Xuhong Li; Aritra Dasgupta; Haoyi Xiong (Atmospheric Environment, 2024)

Chemotaxis gene of a bacterium impacts larval settlement and metamorphosis in the marine mussel Mytilus coruscus via c-di-GMP controlling extracellular protein production - Yu Tao; Jiayi Mu; Lihua Peng; Jin-Long Yang; Xiao Liang (Biofouling, 2024)

Mirids secrete a TOPLESS targeting protein to enhance JA-mediated defense and gossypol accumulation for antagonizing cotton bollworms on cotton plants - Yu-Pei Mu; Dian-Yang Chen; Yu-Jie Liu; Ming-Yu Zhu; Xian Zhang; Yin Tang; Jia-Ling Lin; Mu-Yang Wang; Xiao-Xia Shangguan; Xiao-Ya Chen; Chengshu Wang; Ying-Bo Mao (Molecular Plant, 2024)

Caseinate-coated zein nanoparticles as potential delivery vehicles for guavinoside B from guava: Molecular interactions and encapsulation properties - Haoning Yang; Yu Mu; Dan Zheng; Tess Puopolo; Lejie Zhang; Zhuo Zhang; Sai Gao; Navindra P. Seeram; Hang Ma; Xueshi Huang; Liya Li (Food Chemistry, 2024)

N-doped carbon achieved by pyrolyzing urea and active carbon for the capacitive deionization coupled PMS oxidation system - Meng Chen; Chenxu Yang; Minghao Yu; Mengyao Han; Zihan Meng; Tian Zhao; Jianrui Niu; Situ Mu; Jing Zhang; Junjun Ma; Chun Liu (Desalination, 2024)

Lowering Schottky barrier in MoC-based cocatalyst via heteroatoms tunning for enhanced photocatalytic hydrogen evolution - Ru-zhou Miao; Yu-long Bao; Guang Yang; Ying-jie Sun; Xiao-jing Wang; Jun Zhao; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Multi-chamber membrane capacitive deionization coupled with peroxymonosulfate to achieve simultaneous removal of tetracycline and peroxymonosulfate reaction byproducts - Minghao Yu; Chenxu Yang; Meng Chen; Yunke Li; Kexin Kang; Cheng Wang; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Journal of Hazardous Materials, 2024)

Methanogenic biodegradation of thermoplastic poly(vinyl alcohol) films produced by two manufacturing processes in enrichment cultures - Ming-Le Ji; Yi-Fan Liu; Yu Bai; Zhen Hu; James H. Wang; Jia-Yi Li; Wan-Qi Qin; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Yingcheng Li; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

High-quality acrylic fibers from waste textiles - Bingnan Mu; Xiaoqing Yu; Yuanyi Shao; Yiqi Yang (Science of The Total Environment, 2024)

Insights into atmospheric trace gases, aerosols, and transport processes at a high-altitude station (2623 m a.s.l.) in Northeast Asia - Ye Shan; Yujiao Zhu; Yanbi Qi; Yu Yang; Jiangshan Mu; Mingxuan Liu; Hongyong Li; Ji Zhang; Yanqiu Nie; Yuhong Liu; Min Zhao; Xin Zhang; et al. (Atmospheric Environment, 2024)

Berberine alleviated contrast-induced acute kidney injury by mitophagy-mediated NLRP3 inflammasome inactivation in a mice model - Yalin Yang; Shuang Jiang; Yu Mu; Chilu Liu; Yanxing Han; Jiandong Jiang; Yuhong Wang (Toxicology and Applied Pharmacology, 2024)

Associations of coal mine dust exposure with arterial stiffness and atherosclerotic cardiovascular disease risk in chinese coal miners - Xuezan Huang; Min Mu; Bin Wang; Haozhe Zhang; Yang Liu; Linling Yu; Min Zhou; Jixuan Ma; Dongming Wang; Weihong Chen (International Archives of Occupational and Environmental Health, 2024)

Inhibiting advanced glycation end products (AGEs) of high-performance hemodialysis membranes self-assembled by gallic acid and Ti3C2Tx MXene - Qiqi Wang; Changjun Mu; Ya'nan Yu; Xia Feng; Yang He; Li Chen (Chemical Engineering Journal, 2024)

Nb2CTx MXene coating with inhibition of oxidative stress prepared by Marangoni effect for hemodialysis therapy - Yang He; Hanshu Sun; Yanjie Wang; Ya'nan Yu; Changjun Mu; Li Chen (Chemical Engineering Journal, 2024)

Lactiplantibacillus plantarum DLPT4 Protects Against Cyclophosphamide-Induced Immunosuppression in Mice by Regulating Immune Response and Intestinal Flora - Yinglong Song; Mengying Sun; Fenglian Ma; Dongxue Xu; Guangqing Mu; Yang Jiao; Ping Yu; Yanfeng Tuo (Probiotics and Antimicrobial Proteins, 2024)

Development and evaluation of a haplotype reference panel of Zhikong scallop (Chlamys farreri) for genotype imputation - Mingyi Sui; Zhi Liu; Xiaowen Huang; Zujing Yang; Haitao Yu; Chang Cui; Yuqing Hu; Xuefeng Wang; Xiaojing Shen; Qianqian Mu; Mingxuan Teng; Ang Zhao; et al. (Aquaculture, 2024)

Effects of electron acceptors and donors on anaerobic biodegradation of PAHs in marine sediments - Qingguo Chen; Zhenzhen Li; Yu Chen; Mei Liu; Qiao Yang; Baikang Zhu; Jun Mu; Lijuan Feng; Zhi Chen (Marine Pollution Bulletin, 2024)

Continuously spun biocomposite fibers from feather keratin and chitin with better toughness than wool via enhanced protein unfolding and conformation organization - Bingnan Mu; Xiaoqing Yu; Yiqi Yang (Chemical Engineering Journal, 2024)

Genome-wide identification of GATA transcription factor family and the effect of different light quality on the accumulation of terpenoid indole alkaloids in Uncaria rhynchophylla - Yingying Shao; Yu Zhou; Li Yang; Detian Mu; Iain W. Wilson; Yao Zhang; Lina Zhu; Xinghui Liu; Ling Luo; Jialong He; Deyou Qiu; Qi Tang (Plant Molecular Biology, 2024)

Impacts of seasonality, drought, nitrogen fertilization, and litter on soil fluxes of biogenic volatile organic compounds in a Mediterranean forest - Kaijun Yang; Joan Llusià; Catherine Preece; Roma Ogaya; Laura Márquez Tur; Zhaobin Mu; Chengming You; Zhenfeng Xu; Yu Tan; Josep Peñuelas (Science of The Total Environment, 2024)

Gestational exposure to 1-NP induces ferroptosis in placental trophoblasts via CYP1B1/ERK signaling pathway leading to fetal growth restriction - Shuping Yu; Yaming Mu; Kai Wang; Ling Wang; Chunying Wang; Zexin Yang; Yu Liu; Shuxian Li; Meihua Zhang (Chemico-Biological Interactions, 2024)

Complete recycling of polymers and dyes from polyester/cotton blended textiles via cost-effective and destruction-minimized dissolution, swelling, precipitation, and separation - Bingnan Mu; Xiaoqing Yu; Yuanyi Shao; Lauren McBride; Hannah Hidalgo; Yiqi Yang (Resources, Conservation and Recycling, 2023)

Targeting mitophagy for neurological disorders treatment: advances in drugs and non-drug approaches - Xiong Yang; Yu Zhang; Jia-xin Luo; Tao Zhu; Zhao Ran; Ben-Rong Mu; Mei-Hong Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Sustainable and green process for recycling waste wool textiles into high-quality protein fibers on a pilot scale - Bingnan Mu; Xiaoqing Yu; Yiqi Yang (Resources, Conservation and Recycling, 2023)

Geochronology and in-situ apatite geochemistry of late Paleoproterozoic A-type granites in the Jiao-Liao-Ji Belt, North China Craton: Implications for petrogenesis and tectonic evolution - Yi-Kang Quan; Mao-Song Mu; De-Bin Yang; Xiang-Yu Yan; An-Qi Wang; Le-Ran Hao; Feng Wang (Geochemistry, 2023)

Profitable and environmentally responsible recycling of fibers and reactive dyes from afterlife cotton textiles via controlled dye hydrolysis, fiber swelling and dissolution - Bingnan Mu; Xiaoqing Yu; Yuanyi Shao; Lauren McBride; Hannah Hidalgo; Yiqi Yang (Chemical Engineering Journal, 2023)

Incomplete recovery of gut microbiota in marine medaka (Oryzias melastigma) during the depuration phase, after exposure to sulfamethazine/nanoplastics - Feipeng Wang; Chaoyue Zhang; Shujie Cai; Jingyu Yang; Faguang Li; Xiaofan Liu; Yu Ting Zhang; Jingli Mu (Science of The Total Environment, 2023)

Human footprints in the Global South accelerate biomass carbon loss in ecologically sensitive regions - Mengqing Geng; Xuecao Li; Haowei Mu; Guojiang Yu; Li Chai; Zhongwen Yang; Haimeng Liu; Jianxi Huang; Han Liu; Zhengshan Ju (Global Change Biology, 2023)
Human activities have placed significant pressure on the terrestrial biosphere, leading to ecosystem degradation and carbon losses. However, the full impact of these activities on terrestrial biomass carbon remains unexplored. In this study, we examined changes in global human footprint (HFP) and human‐induced aboveground biomass carbon (AGBC) losses from 2000 to 2018. Our findings show an increasing trend in HFP globally, resulting in the conversion of wilderness areas to highly modified regions. These changes have altered global biomes' habitats, particularly in tropical and subtropical regions. We also found accelerated AGBC loss driven by HFP expansion, with a total loss of 19.99 ± 0.196 PgC from 2000 to 2018, especially in tropical regions. Additionally, AGBC is more vulnerable in the Global South than in the Global North. Human activities threaten natural habitats, resulting in increasing AGBC loss even in strictly protected areas. Therefore, scientifically guided planning of future human activities is crucial to protect half of Earth through mitigation and adaptation under future risks of climate change and global urbanization.

Correction: Three-Dimensional Digital Reconstruction of the Cerebellar Cortex: Lobule Thickness, Surface Area Measurements, and Layer Architecture - Junxiao Zheng; Qinzhu Yang; Nikos Makris; Kaibin Huang; Jianwen Liang; Chenfei Ye; Xiaxia Yu; Mu Tian; Ting Ma; Tian Mou; Wenlong Guo; Ron Kikinis; et al. (The Cerebellum, 2023)

Molecular mechanism by which StSN2 overexpression inhibits the enzymatic browning of potato - Li-qin Li; Yu-lu Mu; Jing Chen; Qiang Wang; Yi-fei Lu; Sun Xin; Shi-min Yang; Xue-li Huang; Xi-yao Wang; Li-ming Lu (Postharvest Biology and Technology, 2023)

Transcriptomic analysis of the fat body of resistant and susceptible silkworm strains, Bombyx mori (Lepidoptera), after oral treatment with fenpropathrin - Zi-qin Zhao; Kai-yi Zheng; Yu-tong Zhu; Jun-li Lv; Zhi-hao Su; Xiao-ying Zhang; Wen-qing Lai; Mu-wang Li; Yang-chun Wu; Xue-yang Wang (Pesticide Biochemistry and Physiology, 2023)

Crop productivity and soil inorganic carbon change mediated by enhanced rock weathering in farmland: A comparative field analysis of multi-agroclimatic regions in central China - Fuxing Guo; Yanping Wang; Haoyong Zhu; Chuangye Zhang; Haowei Sun; Zhuling Fang; Jing Yang; Linsen Zhang; Yan Mu; Yu Bon Man; Fuyong Wu (Agricultural Systems, 2023)

Genome-Wide DNA Methylation Dynamics During Drought Responsiveness in Tibetan Hulless Barley - Dunzhu Jiabu; Mingzhai Yu; Qijun Xu; Haizhen Yang; Wang Mu; Yuzhen Basang (Journal of Plant Growth Regulation, 2023)
Differences in drought stress tolerance within diverse grass genotypes have been attributed to epigenetic modifications. DNA methylation is an important epigenetic alteration regulating responses to drought stress. However, its effects on drought tolerance are poorly understood in Tibetan hulless barley. Here, bisulfite sequencing was conducted to profile the DNA methylation patterns of drought-tolerant variety (XL) and drought-sensitive (DQ) under drought and control conditions. A total of 5843 million reads were generated. We found the significant genome-wide changes in CHH methylation rates between XL and DQ, while CG or CHG methylation rates did not. Besides that, the two contrasting varieties do reveal distinct responses to drought stress in antioxidant activities and differentially methylated regions (DMRs). Genes in drought-tolerant varieties XL are rapidly and significantly methylated when exposed to drought stimulus. These DMRs-related genes in XL are significantly enriched in defense response and response to stimuli via gene-ontology enrichment analysis. Then, we focused on 1003 transcription factors and identified 15 specific DMRs-related transcription factors exhibiting specific methylation changes under drought stimuli. Finally, we identified three DMRs-related TFs ( HvRR12, HvRR2, and HvCSP41B ), where Arabidopsis homologs involve in responses to drought conditions. Altogether, abiotic stresses could be rapidly respond and mediated by methylation of transcription factors in hulless barely.

Dysfunction of NRG1/ErbB4 Signaling in the Hippocampus Might Mediate Long-term Memory Decline After Systemic Inflammation - Yu-zhu Gao; Xin-miao Wu; Zhi-qiang Zhou; Pan-miao Liu; Jian-jun Yang; Mu-huo Ji (Molecular Neurobiology, 2023)

Analysis of oil synthesis pathway in Cyperus esculentus tubers and identification of oleosin and caleosin genes - Youcheng Zhu; Ying Wang; Zunmiao Wei; Xiaokai Zhang; Bingyang Jiao; Yu Tian; Fan Yan; Jingwen Li; Yajing Liu; Xuguang Yang; Jinhao Zhang; Xinyue Wang; et al. (Journal of Plant Physiology, 2023)

Autochthonous bioaugmentation accelerates phenanthrene degradation in acclimated soil - Haiping Gu; Jie Yan; Yuhao Liu; Xuewei Yu; Yan Feng; Xuanyi Yang; Su Shiung Lam; Mu. Naushad; Cheng Li; Christian Sonne (Environmental Research, 2023)

The preliminary study of exosomes derived from thymosin beta 4-treated adipose-derived stem cells in fat grafting - Wandi Li; Yan Yang; Xiaoyu Zhang; Yan Lin; Haoran Li; Yu Yao; Dali Mu (Genes & Genomics, 2023)

Changes in cropland soil carbon through improved management practices in China: A meta-analysis - Bai-Jian Lin; Ruo-Chen Li; Mu-Yu Yang; Zheng-Rong Kan; Ahmad Latif Virk; Yves N′Dri Bohoussou; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Journal of Environmental Management, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Alleviation of substrate inhibition in an anaerobic ammonia oxidation reactor: Recovery process performance and microbial community - Genwang Chang; Yu Yang; Yifei Yang; Jinjin Yang; Shaokang Li; Xiaoying Mu; Jingwen Luo; Xiang Li (Journal of Water Process Engineering, 2023)

A novel bioelectrochemical strategy for efficient treatment of saline-alkaline and oligotrophic sulfate wastewater mediated by bacterial electron shuttling - Hongyan Shen; Zhitao Zhang; Zheng Chen; Jiachang Shen; Qifeng Wen; Yunpu Jia; Chenxi Yu; Gaojie Wei; Tingzhen Mu; Delu Miao; Maohua Yang; Jianmin Xing (Journal of Water Process Engineering, 2023)

Considering spatio-temporal dynamics of soil water with evapotranspiration partitioning helps to clarify water utilization characteristics of summer maize under deficit irrigation - Jiatun Xu; Qing Mu; Yibo Ding; Shikun Sun; Yufeng Zou; Lianyu Yu; Pengyan Zhang; Nan Yang; Wei Guo; Huanjie Cai (Journal of Hydrology, 2023)

Facile synthesis of spiro-core-based hole-transporting material for high-performance and stable perovskite solar cells - Kun-Mu Lee; Seid Yimer Abate; June Hung Yang; Wei-Hao Chiu; Seoungjun Ahn; Sie-Rong Li; Kang-Ling Liau; Yu-Tai Tao; Yan-Duo Lin (Chemical Engineering Journal, 2023)

Bio-inspired supramolecular metallopeptide hydrogel promotes recovery from cutaneous wound - Yun Li; Xiaoyao Cai; Zhilong Wang; Yu Han; Chunhua Ren; Lijun Yang; Zhongyan Wang; Ganen Mu; Haixue Jia; Jianfeng Liu; Jinjian Liu; Cuihong Yang (Chemical Engineering Journal, 2023)

miR-182-5p Delivered by Plasma Exosomes Promotes Sevoflurane-Induced Neuroinflammation and Cognitive Dysfunction in Aged Rats with Postoperative Cognitive Dysfunction by Targeting Brain-Derived Neurotrophic Factor and Activating NF-κB Pathway - Fu-sheng Wei; Mu-wen Rao; Yuan-lu Huang; Shi-biao Chen; Yu-qian Wu; Lei Yang (Neurotoxicity Research, 2022)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Effects of tillage and cropping sequences on crop production and environmental benefits in the North China Plain - Wen-Xuan Liu; Wen-Sheng Liu; Mu-Yu Yang; Yu-Xin Wei; Zhe Chen; Ahmad Latif Virk; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Environmental Science and Pollution Research, 2022)

Linkages among the functional traits, insect visitation rate and seed set of Gentiana taxa on the Tibetan Plateau - Wen-fei Dai; Rui Gao; Meng-ying He; Yu-lian Yang; Fang-lan Li; Jun-peng Mu (Journal of Mountain Science, 2022)

Three-Dimensional Digital Reconstruction of the Cerebellar Cortex: Lobule Thickness, Surface Area Measurements, and Layer Architecture - Junxiao Zheng; Qinzhu Yang; Nikos Makris; Kaibin Huang; Jianwen Liang; Chenfei Ye; Xiaxia Yu; Mu Tian; Ting Ma; Tian Mou; Wenlong Guo; Ron Kikinis; et al. (The Cerebellum, 2022)
The cerebellum is ontogenetically one of the first structures to develop in the central nervous system; nevertheless, it has been only recently reconsidered for its significant neurobiological, functional, and clinical relevance in humans. Thus, it has been a relatively under-studied compared to the cerebrum. Currently, non-invasive imaging modalities can barely reach the necessary resolution to unfold its entire, convoluted surface, while only histological analyses can reveal local information at the micrometer scale. Herein, we used the BigBrain dataset to generate area and point-wise thickness measurements for all layers of the cerebellar cortex and for each lobule in particular. We found that the overall surface area of the cerebellar granular layer (including Purkinje cells) was 1,732 cm 2 and the molecular layer was 1,945 cm 2 . The average thickness of the granular layer is 0.88 mm (± 0.83) and that of the molecular layer is 0.32 mm (± 0.08). The cerebellum (both granular and molecular layers) is thicker at the depth of the sulci and thinner at the crowns of the gyri. Globally, the granular layer is thicker in the lateral-posterior-inferior region than the medial-superior regions. The characterization of individual layers in the cerebellum achieved herein represents a stepping-stone for investigations interrelating structural and functional connectivity with cerebellar architectonics using neuroimaging, which is a matter of considerable relevance in basic and clinical neuroscience. Furthermore, these data provide templates for the construction of cerebellar topographic maps and the precise localization of structural and functional alterations in diseases affecting the cerebellum.

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

Alkalibacillus aidingensis sp. nov., an Bacterium Isolated from Aiding Lake in Xinjiang Province, North-West China - Rui Li; Li Yang; Rüdiger Pukall; Meina Neumann-Schaal; Chang-Gai Mu; Yong-Jiang Shi; Yun Wang; Gang-Qiang Jiang; Yu-Guang Zhou; Man Cai; Min Yin; Wen-Yong Zhu; et al. (Current Microbiology, 2021)

Altered dynamics of functional connectivity density associated with early and advanced stages of motor training in tennis and table tennis athletes - Qing Gao; Yue Huang; Yu Xiang; Chengbo Yang; Mu Zhang; Jingpu Guo; Hu Wang; Jiali Yu; Qian Cui; Huafu Chen (Brain Imaging and Behavior, 2021)

Mechanical and Failure Characteristics of Rock-coal-rock Combined Body under Different Strain Rates: A Numerical Study from Micro Perspective - Shu-ning Dong; Ang Li; Ya-dong Ji; Yu-xuan Yang; Qian Mu (Geotechnical and Geological Engineering, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Creation of fertility-restored materials for Ogura CMS in Brassica oleracea by introducing Rfo gene from Brassica napus via an allotriploid strategy - Hai-long Yu; Zhi-yuan Li; Wen-jing Ren; Feng-qing Han; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Yu-mei Liu; Zhi-yuan Fang; Yang-yong Zhang (Theoretical and Applied Genetics, 2020)
Key message Ogura CMS fertility-restored materials, with 18 chromosomes, normal seed setting, stable fertility and closer genetic background to the parent Chinese kale, were successfully developed in B. oleracea via a triploid strategy for the first time. Abstract Ogura cytoplasmic male sterility (CMS) is the most widely used sterile type in seed production for commercial hybrids of Brassica oleracea vegetables. However, the natural Ogura CMS restorer line has not been found in B. oleracea crops. In this study, the triploid strategy was used with the aim to create euploid B. oleracea progenies with the Rfo gene. The allotriploid AAC hybrid YL2 was used as a male parent to backcross with Ogura CMS Chinese kale. After successive backcrosses, the BC 2 Rfo -positive individual 16CMSF2-11 and its BC 3 progenies, with 18 chromosomes, were developed, which were morphologically identical to the parent Chinese kale. Compared with F 1 and BC 1 plants, it showed stable fertility performance, and regular meiosis behavior and could produce seeds normally under natural pollination. The genomic composition analysis of Rfo -positive progenies by using molecular markers showed that more than 87% of the C-genome components of BC 3 Rfo -progenies recovered to the parent Chinese kale, while most or all of the A n -genome segments were lost in 16CMSF2-11 and its progenies. The results suggested that the genetic background of Rfo -positive individuals was closer to that of the parent Chinese kale along with backcrossing. Hereof, the Ogura CMS fertility-restored materials of Chinese kale were successfully created via triploid strategy for the first time, providing a bridge for utilizing the Ogura CMS B. oleracea germplasm in the future. Moreover, our study indicates that the triploid strategy is effective for transferring genes from B. napus into B. oleracea .

Kompetitive allele-specific PCR (KASP) genotyping and heterotic group classification of 244 inbred lines in cabbage (Brassica oleracea L. var. capitata) - Zhiyuan Li; Hailong Yu; Xing Li; Bin Zhang; Wenjing Ren; Xiaoping Liu; Zhiyuan Fang; Limei Yang; Mu Zhuang; Honghao Lv; Yangyong Zhang (Euphytica, 2020)

The Activation of Heat-Shock Protein After Copper(II) and/or Arsenic(III)-Induced Imbalance of Homeostasis, Inflammatory Response in Chicken Rectum - Xin Yang; Hongjing Zhao; Yu Wang; Juanjuan Liu; Menghao Guo; Dongxue Fei; Mengyao Mu; Mingwei Xing (Biological Trace Element Research, 2020)

Antidepressant Drugs Correct the Imbalance Between proBDNF/p75NTR/Sortilin and Mature BDNF/TrkB in the Brain of Mice with Chronic Stress - C. R. Yang; X. Y. Zhang; Y. Liu; J. Y. Du; R. Liang; M. Yu; F. Q. Zhang; X. F. Mu; F. Li; L. Zhou; F. H. Zhou; F. J. Meng; et al. (Neurotoxicity Research, 2020)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

Elemental imbalance elicited by arsenic and copper exposures leads to oxidative stress and immunotoxicity in chicken gizzard, activating the protective effects of heat shock proteins - Menghao Guo; Hongjing Zhao; Yu Wang; Juanjuan Liu; Dongxue Fei; Xin Yang; Mengyao Mu; Mingwei Xing (Environmental Science and Pollution Research, 2019)

Numerical investigation on a grouting mechanism with slurry-rock coupling and shear displacement in a single rough fracture - Wenqiang Mu; Lianchong Li; Tianhong Yang; Guofeng Yu; Yunchun Han (Bulletin of Engineering Geology and the Environment, 2019)

Comparative transcriptome analysis of cabbage (Brassica oleracea var. capitata) infected by Plasmodiophora brassicae reveals drastic defense response at secondary infection stage - Yu Ning; Yong Wang; Zhiyuan Fang; Mu Zhuang; Yangyong Zhang; Honghao Lv; Yumei Liu; Zhansheng Li; Limei Yang (Plant and Soil, 2019)

Geosites in Karamay city, Xinjiang Uygur Autonomous Region, northwest China - Jun-Ting Qiu; Liang Qiu; Hong-Xu Mu; Wen-Xin Yang; Feng Chen; Bo-Kun Yan; Jun-Chuan Yu; He-Ming Yang (Geoheritage, 2019)

Anti-breast cancer triterpenoid saponins from the thorns of Gleditsia sinensis - Jinqian Yu; Gang Li; Yan Mu; Honglei Zhou; Xiao Wang; Peng Yang (Natural Product Research, 2019)

Identification of a major QTL for seed number per silique in cabbage (Brassica oleracea L. var. capitata) using genotyping by sequencing - Xing Li; Congcong Kong; Hailong Yu; Xiaoping Liu; Zhiyuan Fang; Yumei Liu; Limei Yang; Mu Zhuang; Yong Wang; Honghao Lv; Yangyong Zhang (Euphytica, 2019)

Astaxanthin enhances hematology, antioxidant and immunological parameters, immune-related gene expression, and disease resistance against in Channa argus - Mu-Yang Li; Xin-Yu Liu; Chang-Ge Xia; Gui-Qin Wang; Dong-Ming Zhang (Aquaculture International, 2019)

Tilapia fisheries in Guangdong Province, China: Socio‐economic benefits, and threats on native ecosystems and economics - Dang En Gu; Fan Dong Yu; Ye Xin Yang; Meng Xu; Hui Wei; Du Luo; Xi Dong Mu; Yin Chang Hu (Fisheries Management and Ecology, 2019)
Tilapia is one of the groups of fish species most widely cultured globally. China has been the largest producer of tilapia in the world since 1990s. Guangdong Province produces almost 40% of all tilapia in China because of its suitable geography and weather conditions, and tilapia culture has brought considerable economic benefits. Unfortunately, many of the biological traits that make tilapia popular for culture also contribute to its success as an invader. Tilapia has invaded natural waters and has become the dominant fish in many rivers of Guangdong Province, causing economic loss in capture fisheries, and affecting native fish species, biodiversity and aquatic ecosystems. Poor fishery management, water quality degradation and biodiversity loss have all facilitated the tilapia invasion. Tilapia have filled the niches left vacant by now locally extinct native species resulting from environmental changes in freshwater ecosystems of the province. The introduction of tilapia has both advantages and disadvantages, which should be managed to use effectively the various tilapia species in aquaculture while controlling their spread in natural waters.

Regulatory Roles of Peroxisomal Metabolic Pathways Involved in Musk Secretion in Muskrats - Meishan Zhang; Shuang Yang; Minghui Shi; Shumiao Zhang; Tianxiang Zhang; Yimeng Li; Shanghua Xu; Muha Cha; Yuping Meng; Shaobi Lin; Juan Yu; Xuxin Li; et al. (The Journal of Membrane Biology, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Efficiency of sequential UV/H2O2 and biofilm process for the treatment of secondary effluent - Peng-Fei Yan; Shoujun Yuan; Wei Wang; Zhen-Hu Hu; Yang Mu; Han-Qing Yu (Environmental Science and Pollution Research, 2019)

Identification and characterization of resistance for Plasmodiophora brassicae race 4 in cabbage (Brassica oleracea var. capitata) - Yu Ning; Yong Wang; Zhiyuan Fang; Mu Zhuang; Yangyong Zhang; Honghao Lv; Yumei Liu; Zhansheng Li; Limei Yang (Australasian Plant Pathology, 2018)

Dose Verification for Tumor Motion with Different Treatment Planning Systems: A Dynamic Thorax Phantom Study - Shih-Neng Yang; Chun-Wei Lin; Mu-Bai Chang; Geoffrey G. Zhang; Kuei-Ting Chou; Yu-Rou Chiou; Shung-Shung Sun; Louis Lui; Tsung-Jung Ho; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Fish invasion in the river systems of Guangdong Province, South China: Possible indicators of their success - D. E. Gu; Y. C. Hu; M. Xu; H. Wei; D. Luo; Y. X. Yang; F. D. Yu; X. D. Mu (Fisheries Management and Ecology, 2018)
Although a large number of fish species have been introduced into Guangdong Province in Southern China, a few species, such as tilapia ( Tilapia spp.), North African catfish Clarias gariepinus Burchell, mrigal carp, Cirrhinus mrigala (Bloch) and the sucker mouth catfish ( Hypostomus sp.), have established natural populations and can be considered “successful invaders” in large rivers. The specific mechanisms underlying these contrasting results among different introduced fish species remain understudied. The relationship between multiple abiotic–biotic factors and the success of four invasive species was investigated using survey data for the Guangdong Province river ecosystem. In contrast to previous studies that have considered species‐specific traits, the focus was on economic, ecological and anthropogenic factors to predict invasion success. Four main predictive indicators were found: (1) successful invaders were of low or no commercial value; (2) successful invaders tolerated a wide range of environmental conditions, including poor water quality; (3) biodiversity loss accelerated the growth of non‐native populations; (4) human disturbance facilitated population growth and spread of invasive fish species. To lessen the impacts of invasive fish species, the selection of breeding species and breeding areas, maintenance of water quality and reduction in water pollution, protection of the diversity of fish species and reduction of human interference should be addressed.

Recessive male sterility in cabbage (Brassica oleracea var. capitata) caused by loss of function of BoCYP704B1 due to the insertion of a LTR-retrotransposon - Jia-lei Ji; Li-mei Yang; Zhi-yuan Fang; Mu Zhuang; Yang-yong Zhang; Hong-hao Lv; Yu-mei Liu; Zhan-sheng Li (Theoretical and Applied Genetics, 2017)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

Reactive Oxygen Species-mediated Loss of Phenotype of Parvalbumin Interneurons Contributes to Long-term Cognitive Impairments After Repeated Neonatal Ketamine Exposures - Hui Zhang; Xiao-ru Sun; Jing Wang; Zhen-zhen Zhang; Hong-ting Zhao; Hui-hui Li; Mu-huo Ji; Kuan-yu Li; Jian-jun Yang (Neurotoxicity Research, 2016)

A graphical model for haloanhydrite components and P-wave velocity: A case study of haloanhydrites in Amu Darya Basin - Tong-Cui Guo; Hong-Jun Wang; Long-Xin Mu; Xing-Yang Zhang; Zhi Ma; Yu Tian; Hao-Chen Li (Applied Geophysics, 2016)

Development of a novel allele-specific Rfo marker and creation of Ogura CMS fertility-restored interspecific hybrids in Brassica oleracea - Hai-long Yu; Zhi-yuan Fang; Yu-mei Liu; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Yang-yong Zhang (Theoretical and Applied Genetics, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Prevalence, quantification, and typing of human adenoviruses detected in river water in Taiwan - Zhon-Min Huang; Bing-Mu Hsu; Po-Min Kao; Tien-Yu Chang; Tsui-Kang Hsu; Ying-Ning Ho; Yi-Chun Yang; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

Breeding of cabbage (Brassica oleracea L. var. capitata) with fusarium wilt resistance based on microspore culture and marker-assisted selection - Hong-hao Lv; Qing-biao Wang; Li-mei Yang; Zhi-yuan Fang; Yu-mei Liu; Mu Zhuang; Yang-yong Zhang; Yu-hong Yang; Bing-yan Xie; Xiao-wu Wang (Euphytica, 2014)

The role of mast cells in ischemia and reperfusion injury - Mu-qing Yang; Yuan-yuan Ma; Jing Ding; Ji-yu Li (Inflammation Research, 2014)

Inhibiting mast cell degranulation by HO-1 affects dendritic cell maturation in vitro - Yuan-yuan Ma; Mu-qing Yang; Chun-feng Wang; Jing Ding; Ji-yu Li (Inflammation Research, 2014)

Intraperitoneal delivery of paclitaxel by poly(ether-anhydride) microspheres effectively suppresses tumor growth in a murine metastatic ovarian cancer model - Ming Yang; Tao Yu; Joseph Wood; Ying-Ying Wang; Benjamin C. Tang; Qi Zeng; Brian W. Simons; Jie Fu; Chi-Mu Chuang; Samuel K. Lai; T.-C. Wu; Chien-Fu Hung; et al. (Drug Delivery and Translational Research, 2014)

A correlation between acute kidney injury and myonecrosis after scheduled percutaneous coronary intervention - Min Zhang; Hao-yu Meng; Ying-ming Zhao; Zhi-wen Tao; Xiao-xuan Gong; Ze-mu Wang; Bo Chen; Zheng-xian Tao; Chun-jian Li; Tie-bing Zhu; Lian-sheng Wang; Zhi-jian Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Repeat oral dose toxicity studies of melamine in rats and monkeys - Richard J. Early; Hong Yu; Xueyan Peter Mu; Haiyan Xu; Lei Guo; Qingxue Kong; Junma Zhou; Bruce He; Xiuying Yang; Hailiang Huang; Edward Hu; Ying Jiang (Archives of Toxicology, 2013)

Significantly differential diffusion of neuropathological aggregates in the brain of transgenic mice carrying N-terminal mutant huntingtin fused with green fluorescent protein - Pei-Hsun Cheng; Chia-Ling Li; Lu-Shiun Her; Yu-Fan Chang; Anthony W. S. Chan; Chuan-Mu Chen; Shang-Hsun Yang (Brain Structure and Function, 2013)

Effects of pH, MES, arabinogalactan-proteins on microspore cultures in white cabbage - Su-xia Yuan; Yan-bin Su; Yu-mei Liu; Zhi-yuan Fang; Li-mei Yang; Mu Zhuang; Yang-yong Zhang; Pei-tian Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

A fully human CD19/CD3 bi-specific antibody triggers potent and specific cytotoxicity by unstimulated T lymphocytes against non-Hodgkin’s lymphoma - Yan Zhou; Lan-tu Gou; Bo Mu; Wei-chan Liao; Jing He; Cong Ma; Yu-qin Yao; Jin-liang Yang (Biotechnology Letters, 2012)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

PM2.5 and Associated Polycyclic Aromatic Hydrocarbon and Mutagenicity Emissions from Motorcycles - Hsi-Hsien Yang; Shu-An Lee; Dennis P. H. Hsieh; Mu-Rong Chao; Che-Yu Tung (Bulletin of Environmental Contamination and Toxicology, 2008)

Efficient organogenesis and plantlet regeneration in the timber species Cunninghamia lanceolata (Lamb.) Hook - Mu-lan Zhu; Ji Wang; Yang Yu; Sheng-jun Liu; Zhi-ming Wei (In Vitro Cellular & Developmental Biology - Plant, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)